OpenSEA: a 3D printed planetary gear series elastic actuator for a compliant elbow joint exoskeleton - Benjamin Jenks; Benjamin Jenks; Hailey Levan; Hailey Levan; Filip Stefanovic (Frontiers in Robotics and AI)
IntroductionNext-generation assistive robotics rely on series elastic actuators (SEA) that enable compliant human-robot interaction. However, currently there is a deficiency of openly available SEA systems to support this development. To address this, we propose a novel design of a compliant 3D-printed SEA device for elbow movement rehabilitation exoskeletons that we make openly available.MethodsWe designed a 3D-printed SEA to incorporate a planetary gear system and torsional spring, offering compliance, adaptability, and cost-effectiveness. The design provides a high-power density, that can address torque limitations in 3D printed SEA systems. Our design utilizes a 4.12 Nm motor operating at 26 RPM based on assessment of functional performance differences across healthy and post-stroke individuals. Moreover, the design of this SEA allows for easily adjustable parameters to fit different joints, or various torque output configurations, in low-cost exoskeleton applications in rehabilitation.ResultsTesting demonstrated an average compliance contribution of the planetary gear and the average total system compliance of 14.80° and 22.22°, respectively. This range conforms to those expected in human-exoskeleton interaction. Similarly, an FEA analysis of the 3D printed system shows stress ranges of the SEA gears to be between 50 and 60.2 MPa, which causes a displacement of approximately 0.14 mm. This is within the operational flexural range of standard 3D printed materials such as PLA, which is 175 MPa.DiscussionThe study demonstrates an openly available SEA design for 3D printed exoskeletons. This work provides an entry point for accessible exoskeleton design, specifically for rehabilitation. Future work will explore the role of segment vs joint rigidity in developing next-generation compliant exoskeletons, and improving accessibility for personalizable assistive exoskeletons. All designs presented herein are publicly available.